(untitled) - Helmut F van Emden (Cambridge, New York, 1989)
The book discusses how far chemical control has created problems and how far these may be solved by further chemical control or by alternative methods. The reasons why insects are pest problems are discussed so that the ecological merits and demerits of the various control methods can be assessed. Stress is laid on both the biotic and economic environments in which pest control has to operate
Keywords: pests control